Flow Characteristic of Variable Diameter Capillary Tube for Heat-pump Air Conditioner with R410A - He Qinbo; Yan Geni; Xu Yansheng (Zhileng xuebao)
A variable diameter capillary tube consisting of two serially connected capillary tubes with different diameters was invented to replace a conventional expansion device. The mass flow rates of refrigerant R410A in variable diameter capillary tubes with various sizes were tested. A model of the variable diameter capillary tube is proposed, and a numerical algorithm for the tube length and mass flow rate is developed. The experimental results show that, in a performance comparison between a variable diameter capillary tube system and a capillary tube assembly system, the cooling capacity of the former is reduced by 0.3%, their energy efficiency ratio (EER) is equal, the heating capacity is increased by 0.3%, and the coefficient of performance (COP) is decreased by 0.3%. That is, the performance index of the two kinds of throttle mechanism is almost identical. This indicates that the variable diameter capillary tube can completely replace the capillary tube assembly in an R410A heat pump type air conditioner. The model is validated using experimental data, and the results show that the model can be used for sizing and rating a variable diameter capillary tube.